FAKTOR-FAKTOR YANG MEMPENGARUHI INDEPENDENSI AUDITOR - Dewi Muliyana, 07.05.52.0003; Badjuri, Achmad (Students Journal of Accounting and Banking, 2012)
Independence is the attitude expected of a public accountant for not having a personal interest in the execution of his duty contrary to the principles of integrity and objectivity. Independence must be regarded as one of the characteristic of the most important public accountant. The independence of public accountant includes two aspects: independence in mental attitude and appearance of independence. Independence in mental attitude means of self-honesty in accounting in considering the facts and a consideration of objective, impartial in formulating his opinion, while the appearance if independence means that the public impression that the independent public accountant to act so that public accountants should avoid circumstances of factors, factors that can lead to the dubious freedom. Sample selection methods in the study was conducted using purposive sampling method, the criteria for determining the sample is a public accountant who has had experience doing an audit and have worked for more than 2 years. Numbers of samples obtained were 63 respondents.the data used in this study is the primary data using questionnaires. Analysis of the data which is used multiple linear regression analysis. Hypothesis testing using the test with the test results indicate that the bonds of financial interest and relationships with clients, long-standing relationship with the clientâs auditor, the competition among KAP, social relations and significant negative effect on the appearance of independence of public accountants; provision of services other than audit services, the size of the KAP office, the audit fee does not significantly influence the appearance of independence of public accountants.Keywords: independence, accountants, bond interest, long-standing relationship, competition among KAP, social relations, the rendering of services, the size of the KAP office, the audit fee